Bilateral Lung Transplantation for Congenital Pulmonary Arteriovenous Fistula with Intraoperative Venovenous ECMO Support: The First Case Report in China - Liang, Jialong; Chen, Yuan; Zhou, Jintao; Zheng, Mingfeng; Liu, Feng; Ye, Shugao; Chen, Jingyu; Ji, Yong (Frontiers in Surgery, 2022)
Pulmonary arteriovenous fistula (PAVF) is a rare pulmonary vascular lesion, more than 80% of which is caused by congenital abnormal development of pulmonary capillaries. The incidence of PAVF ranges from 2/100,000 to 3/100,000, with no difference in the male and female ratio. Congenital PAVF is often associated with hereditary hemorrhagic telangiectasia (HHT). In this article, we report a patient with only congenital PAVF that was successfully treated by bilateral lung transplantation (BLT) with intraoperative venovenous extracorporeal membrane oxygenation (ECMO) support because both lungs have been affected by PAVF and secondary pulmonary hypertension. To the best of our knowledge, this is the first report of BLT for PAVF in China and the second report that explains the clinical course of a patient to receive BLT for congenital PAVF without HHT. Some investigators have proposed lung transplantation as a definitive treatment, but the results are controversial. On the basis of the current condition of this patient, we believe lung transplantation is a viable option for certain patients, but the long-term effect remains to be studied.